Use of Geographic Information Systems for Creation of Electronic Database of Anthrax Burial sites in the Stavropol Territory - N. P. Buravtseva; V. M. Mesentsev; А. G. Ryazanova; X. M. Golovinskaya; D. Yu. Degtyarev; A. N. Pazenko; O. I. Semenova; A. N. Kulichenko (Проблемы особо опасных инфекций, 2020)
Objective of the study was to use geographic information systems to create an electronic database of anthrax burials and electronic cadastres in the Stavropol Territory. Materials and methods. ESRI - ArcGIS10 software was used as a GIS platform. Results and discussion. A retrospective analysis of the epizootiologic and epidemiological situation on anthrax in the Stavropol Territory was carried out. It was revealed that 352 anthrax stationary potentially hazardous sites were located in the territory of all 26 districts, in 16 of which 52 were abandoned anthrax burials. The greatest epidemiological risk is posed by 22 cattle burial grounds, in which animal corpses were buried (42.3 %). 30 cattle burial grounds with ash burials (57.7 %) pose a lower potential danger. The arrangement of anthrax burial sites in the Stavropol Territory has a number of disadvantages, only 23 cattle burial grounds (44.2 %) have a satisfactory veterinary and sanitary state. Based on the information obtained, an electronic geographic information database of anthrax cattle burial grounds was created for each district of the Stavropol Territory. The structure of the database is presented in the form of a table, which contains all the basic information about the burial, including geographical coordinates. The information was then entered into the ArcGIS10 program, using the geographical method. Each point, plotted on the map, contains the description of the animal burial ground, presented in the table. Thus, the main layer of the geographic information system is created. It can be overlaid with other layers that carry information about the location of the anthrax stationary potentially hazardous sites, the nature of the soil, objects located in the territory. In addition, electronic cadastral atlases of the location of anthrax cattle burials in each district of the Stavropol territory have been created. Electronic cadastral atlases are easier to use, do not require specialized personnel and applicable computer GIS system, but at the same time can give the necessary information about a particular burial in the Stavropol Territory.